Viperidae snake venom phospholipase A2 . Biochemical targets for the action of protein in the human blood circulatory system. Part 1 (review of literature) - L. V. Galebskaya; L. V. Vasina; M. A. Galkin; Yu. V. Tarasova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Snake venoms have been fervently studied for decades for two reasons: 1) high death rate due to snake bites; 2) numerous components of snake venoms prove useful in medicine and treatment of diverse pathologies. Snake venom phospholipases A2 are among the most aggressive toxic proteins often playing the main role in immobilization and killing of snakebite victims. These enzymes catalyze the hydrolysis of glycerophospholipids to produce lysoglycerophospholipids and free fatty acids. But the diversity of phospholipase A2 effects is not limited to their catalytic action. In this review (Part 1), we describe the features of the structure and properties of Viperidae snake venom phospholipase A2 .